SKRINING FITOKIMIA, UJI ANTIOKSIDAN DAN UJI TOKSISITAS EKSTRAK ETANOL DAUN BINTARO (Cerbera manghas) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Ramadani, Andi Deffi; Aditya, Adrian Maulana; T, Nurnaningsi; Erwin, Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
The purpose of this study was to determine the results of phytochemical tests of bintaro leaf ethanol extract and to determine the results of antioxidant tests using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method with a concentration variation of 100; 80; 60; 40; and 20 ppm obtained from bintaro leaf ethanol extract by testing its toxicity using the Brine Shrimp Lethality Test (BSLT) method. The results showed that the ethanol extract of bintaro leaves (Cerbera manghas) contains steroid compounds, saponins, and quinones. Furthermore, the IC50 value of the ethanol extract of bintaro leaves (C. manghas) was 41.68 ppm with a very strong category and the results of the toxicity test obtained the LC50 value of the ethanol extract of bintaro leaves (C. manghas) of 30.44 ppm with a very toxic category. An extract with an LC50 value ≤ 30 ppm has the potential as an anticancer drug candidate because of the correlation between the level of toxicity and anticancer activity so that these results can be concluded that the ethanol extract of bintaro leaves (C. manghas) has the potential to have bioactivity because it is toxic to Artemia salina L. shrimp larvae. Keywords: Antioxidant, Brine Shrimp Lethality Test (BSLT), Bintaro Leaves, Phytochemical Test